Perianal abscess and fistula in ano: consideraciones diagnósticas y terapéuticas - Bermúdez Villegas, Jorge; Rompani, Omar; Veirano, Gustavo; Gutiérrez, Fernando; Corradi, Daniel (Cirugía del Uruguay, 1983)
After some anatomic and pathogenic comments, the authors have adopted Parks classification pointing some anatomic differences